Numerical Analysis and Testing of Gas Oven - ANDRA FEBRIAN (NIM 13103059), NICKY
An oven is an appliance to cook food by means of passing hot gasses that hails from fuel combustions or electrical energy. The oven that is used as the object of study in this research is an already previously fabricated and produced by other students, which possess a uniform temperature distribution in the oven's interior. In this final project, a numerical analysis is conducted to find the temperature distribution and gas velocity inside the oven to find an oven design which has an even interior temperature. Numerical analysis is conducted by using Fluent and Gambit software's. The oven's geometry is modeled in Gambit and then afterwards it is analyzed by using Fluent. To evaluate the results from the numerical analysis, an experiment is conducted to measure the temperature inside the oven on predetermined points. Temperature is measured by using thermocouples connected to a data acquisition system. Agreement between numerical and experimental results is achieved. Numerical calculation is then carried out to find a better temperature distribution by changing the isolation geometry and the cross section area of the oven's gas inlet. The results shows that the maximum temperature difference inside the oven is 16,1oC for the inlet gas diameter of 7,5 mm each at lower to middle part and 15 mm each at the upper part of the oven.